Development of A Video Tutorial for Making Digital Motif Designs in Class X Busana 1 SMKN 8 Surabaya - Yuma, Shabrina Yasinta Zahra; Arifiana, Deny; Rahayu, Imami Arum Tri; Kharnolis, Mein (PT. Riset Press International, 2024)
Video tutorials are teaching media that can facilitate student learning activities because of their effectiveness and efficiency. The research has the following objectives: 1). the feasibility level of digital motif design video tutorials 2). student learning outcomes after being shown a video tutorial on designing digital motifs. The study employs the ADDIE R&D (Analysis, Design, Development, Implementation, Evaluation) research approach, utilising a one-shot case study research design. The study was conducted from May to November 2023. the study involved 32 students from Clothing Class 1 at SMKN 8 Surabaya. These six students participated in a limited trial. The research also involved two media experts from Surabaya State University and two material experts from SMKN 8 Surabaya lecturers. Collection methods include level evaluation processes such as video tutorials and assignment grading. The form of conformity evaluation of assignment sheets and learning videos serves as a research tool. Using a descriptive data analysis method, the average effectiveness of learning video services and categorise the learning outcomes based on CTF. Results of this study stated: 1. The development of video tutorials for designing digital motifs was declared feasible to implement with a total score of 4.6. The average score of material experts is 4.4, and media experts 4.8 2. Based on the results of class tests, we can resolve using video tutorial media to create digital motif designs as learning.